2019
DOI: 10.1590/1981-6723.28918
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and textural properties of goat’s milk cheese prepared using dahi (yogurt) as the starter culture

Abstract: This study aimed to develop goat’s milk cheese to conserve the major milk constituents. Household dahi (yoghurt) is an inexpensive source of starter cultures that contains several types of microorganism of which most are thermophilic in nature and can be used in the production of goat’s milk cheese. Different concentrations of dahi (0.5%, 1.0%, 1.5%, 2.0% and 2.5%) were used to prepare the cheeses following the standard procedure for cheese manufacturing. The cheeses were analysed for their physicochemical, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Although the total solids and moisture contents were not significantly (P>0.05) affected by the addition of starter culture, total solids (44.27%) content was high in T1 cheese, while the moisture (55.77%) content was high in T2 cheese. These results are in accordance with those of Shabbir et al [30] who reported that the use of starter culture resulted in higher titratable acidity in cheese, which improved the whey separation led to an increase in total solids content.…”
Section: Effect Of Starter Culture On the Physicochemical Characteristics Of Cheesesupporting
confidence: 93%
“…Although the total solids and moisture contents were not significantly (P>0.05) affected by the addition of starter culture, total solids (44.27%) content was high in T1 cheese, while the moisture (55.77%) content was high in T2 cheese. These results are in accordance with those of Shabbir et al [30] who reported that the use of starter culture resulted in higher titratable acidity in cheese, which improved the whey separation led to an increase in total solids content.…”
Section: Effect Of Starter Culture On the Physicochemical Characteristics Of Cheesesupporting
confidence: 93%
“…Moreover, these cheese samples showed an increase in pH values with increasing dosage of calcium added to the milk. In contrast, Shabbir et al [ 72 ] showed that adhesiveness decreased with lower moisture levels in goat cheese.…”
Section: Resultsmentioning
confidence: 95%
“…Higher moisture content tends to result in softer cheese, while increased fat and protein content contribute to a firmer texture. The mineral concentration, particularly calcium, has a vital role in curd formation and subsequent cheese structure development [110,111]. Moreover, the texture of goat cheese plays a crucial role in its sensory attributes [112].…”
Section: Texture Of Cheesementioning
confidence: 99%